The Giver [videorecording (DVD)] - Bridges, Jeff, 1949-; Streep, Meryl; Thwaites, Brenton, 1989-; Lowry, Lois; Bridges, Lloyd (Anchor Bay Entertainment, 2014)
The story centers on Jonas, young man who lives in a supposedly ideal world of conformity and contentment. Yet as he begins to spend time with the elder, who is the sole keeper of all the community's memories, Jonas quickly begins to discover the dark and deadly truths of his community's secret past. At extreme odds, Jonas knows that he must escape their world to protect them all; a challenge that no one has ever succeeded at before.